THE ROLE OF FUTURE TRENDS AND FUTUROLOGICAL COMPETENCE IN IMPROVING STUDENTS' PHYSICAL QUALITIES (American Journal of Pedagogical and Educational Research, 2025)
This article discusses the importance of physical exercises in forming the technical condition of students, the possibilities of using physical exercises in forming the technical condition of students.